The Influence of Variables That Can Affect Firm Value in the Banking Industry on the Indonesia Stock Exchange - Arsyana, Adhyasta Cakra Whisnu; Hwihanus, Hwihanus (Jurnal Keuangan dan Perbankan, 2023)
This study aims to analyze the influence of macro fundamentals and financial risk with capital structure, ownership structure, company characteristics, and financial performance as intervening variables on company value with indicators of stock price, earnings per share, and price to book value. This research is quantitative descriptive with a random sampling technique of ten samples from forty-seven banks in Indonesia in 2019-2022 listed on the Indonesia Stock Exchange. The analysis technique uses Partial least Square (PLS). The results showed that macro fundamentals have a significant effect on company value, company characteristics have a considerable impact on financial performance, financial risk has a significant effect on company characteristics, financial risk has a substantial effect on ownership structure, financial risk has a significant impact on capital structure, and capital structure has a significant effect on financial performance. In addition to the six hypotheses, it shows insignificant, so the company's value is influenced by macro fundamentals, financial risk, capital structure, company characteristics, ownership structure, and financial performance it just 33%. DOI: 10.26905/jkdp.v27i2.11010